PATCH-DP: a single-arm phase II trial of intra-operative application of HEMOPATCH™ to the pancreatic stump to prevent post-operative pancreatic fistula following distal pancreatectomy. Issue 1 (January 2022) - Bubis, Lev D.; Behman, Ramy; Roke, Rachel; Serrano, Pablo E.; Khalil, Jad A.; Coburn, Natalie G.; Law, Calvin H.; Bertens, Kimberly; Martel, Guillaume; Hallet, Julie; Marcaccio, Michael; Balaa, Fady; et al.
Abstract: Background: Post-operative pancreatic fistula (POPF) is the most significant cause of morbidity following distal pancreatectomy. Hemopatch™ is a thin, bovine collagen-based hemostatic sealant. We hypothesized that application of Hemopatch™ to the pancreatic stump following distal pancreatectomy would decrease the incidence of clinically-significant POPF. Methods: We conducted a prospective, single-arm, multicentre phase II study of application of Hemopatch™ to the pancreatic stump following distal pancreatectomy. The primary outcome was clinically-significant POPF within 90 days of surgery. A sample size of 52 patients was required to demonstrate a 50% relative reduction in Grade B/C POPF from a baseline incidence of 20%, with a type I error of 0.2 and power of 0.75. Secondary outcomes included incidence of POPF (all grades), 90-day mortality, 90-day morbidity, re-interventions, and length of stay. Results: Adequate fixation Hemopatch™ to the pancreatic stump was successful in all cases. The rate of grade B/C POPF was 25% (95%CI: 14.0–39.0%). There was no significant difference in the incidence of grade B/C POPF compared to the historical baseline (p = 0.46). The 90-day incidence of Clavien–Dindo grade ≥3 complications was 26.9% (95%CI: 15.6–41.0%). Conclusion: The use of Hemopatch™ was not associated with a decreased incidence of clinically-significant POPF compared to historical rates. (NCT03410914).